Barthesian semiologies on selected YouTube video clips of Petra Mahalimuyak - Liwanag, Leslie Anne L.; Demeterio, Feorillo Petronilo A., III (2016)
Access online through this link: https://www.plarideljournal.org/article/barthesian-semiologies-selected-youtube-video-clips-petra-mahalimuyak
Keywords: Rivera, Ashley; Popular culture; YouTube (Web resource)